Effect of pore size distribution in the gas diffusion layer adjusted by composite carbon black on fuel cell performance. (23rd December 2020) - Lin, Guangyi; Liu, Shouyi; Qu, Guangkai; Song, Yingjie; Li, Tianya; Liu, Fumin; Hu, Yafei
Summary: In this paper, the newly prepared gas diffusion layer (GDL) is investigated and characterized. The GDL mainly includes the carbon paper layer and microporous layer (MPL). By the analysis of physical and electrochemical test results, it is found that the performance of GDL prepared by composite carbon black is obviously improved compared with conventional GDL prepared by single carbon black. This new GDL combines the characteristics of two original carbon materials and has a more reasonable pore structure, which can meet the good transmission of reaction gas and liquid water. Furthermore, the research shows that the pore size distribution of GDL can be effectively adjusted by changing the proportion of composite carbon black. The GDL with composite carbon black consisting of 70 wt.% Acetylene Black carbon and 30 wt.% Vulcan XC‐72 is finally confirmed to have the best fuel cell performance. Abstract : The GDL with carbon paper layer and MPL was prepared. By the analysis of physical and electrochemical test results, it was found that the performance of GDL prepared by composite carbon black was obviously improved compared with conventional GDL prepared by single carbon black. This new GDL combined the characteristics of two original carbon materials and had a more reasonable pore structure, which can meet the good transmission of reaction gas and liquid water. Furthermore, the research showed the pore size distribution of GDL can be effectively adjusted by changing the proportion of composite carbon black.